Оздоблювально-зміцнювальна обробка штовхача клапана ДВЗ - Литовка, Д. Є.; Litovka, D. (Харківський національний автомобільно-дорожній універститет, 2024)
In order to improve the quality, it is proposed to subject the valve pusher of internal combustion engines of road construction and lifting and transport vehicles to finishing and strengthening treatment by surface plastic deformation - hydroblasting.
Finishing and strengthening processing of the push valve of the internal combustion engine
Keywords: штовхач клапана; високоміцний чавун; гідродробострумінна обробка; valve pusher; high-strength cast iron; hydrojet processing.; 621.91.01